ORGANIZATIONAL CLIMATE AND CULTURE: IMPLICATIONS FOR PRACTICE OF EXTRA-HOSPITAL NURSES - Silva, Márcio Daniel Dias de Almeida e; Magalhães, José Fernando da Silva Monteiro Oliveira de; Azevedo, Guilherme Eça Guimarães Gonçalves; Queirós, Cristina; Borges, Elisabete (Cogitare Enfermagem, 2024)
Aim: This study aims to identify the organizational climate and culture among nurses working in Immediate Life Support Ambulances (ILSA). Methods: A descriptive, quantitative, and cross-sectional study was conducted with 81 Portuguese nurses working in Immediate Life Support Ambulances at the National Medical Emergency Institute (INEM). The data was analyzed using the Principal Component Analysis (PCA) method, followed by a Varimax rotation, and the models were validated using the Kaiser-Meyer-Olkin test and Bartlett’s test of sphericity. Findings: Factorial analysis yielded four factors, namely: Support (24.5%), Objectives (13.6%), Rules (9.7%), and Innovation (8.01%), associated with organizational climate and culture. Nurses with an undergraduate degree perceived significantly more support than those with higher qualifications. Support also varied according to relationship status, revealing that married nurses had a higher perception than those cohabiting. Conclusion: Organizational climate and culture unequivocally contribute to developing a healthy and safe work environment and are decisive for the quality of nursing care.